SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SMARTPHONE BERBASIS WEBSITE DENGAN METODE SIMPLE ADDITIVE WEIGTHING - Andika Fakhrizal; Sri Ngudi Wahyuni; Rosyidah Jayanti Vijaya (Hemispheres Press, 2023)
Along with the development of smartphones in Indonesia, people in various circles are very dependent on the use of smartphones. Especially with the current pandemic making people depend on the use of smartphones. With the various brands, types, and specifications of smartphones, people are confused about which smartphones to choose according to their respective needs. From these problems, a website-based decision support system is needed to help and facilitate people in choosing the right smartphone model according to the criteria. The criteria that will be included in this system are price, brand, RAM, storage, camera, battery screen, and features. The purpose of this thesis is to build a system that can help people find smartphones that match the required criteria. This system uses the Simple Additive Weighting (SAW) method which is used to normalize the weights of the inputted criteria and to determine the highest smartphone value as a recommendation option. The results of this study are the creation of a smartphone selection decision support system with the website-based Simple Additive Weighting method that can provide recommendations for smartphone types according to their respective needs.